Microfinance : An Innovative Tool for Women Empowerment in Rural Area - Ranjan, Saroj (Journal of Commerce and Trade, 2009)
Women are identified as a mother, a wife, sister, daughter and daughter in law but she is not treated as independent person. Women have remained backward owing to many factors the scriptures laid down an exalted status for them .in recent year , there has been an increasing awareness and recognition of the fact that women who formed half of the society can’t be ignored . Government initiates many policies for betterment of women status in society &for empowerment. Microfinance programmes for women are increasingly seen by development agencies as an effective poverty alleviation intervention, with a positive impact on economic growth and number of social development indicators. High repayment rates are interpreted to mean that women are using loans productivity and controlling credit. It is widely assumed that there is a clear and direct relationship between access to credit and increase in the status of women within their house holds and communities, provision of credit is believed to lead to empowerment of women. This paper reflects on women as a primary strategy for addressing poverty & empowerment.